Teacher Strategies in the Center-Based Learning Model within the Merdeka Curriculum at TK Bungong Seleupoek - Daulay, Al-Aura Zahra; Fitriani, Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to describe teachers’ strategies in implementing the center-based learning model at TK Bungong Seleupoek within the framework of the Merdeka Curriculum. The research employed a descriptive qualitative approach using a case study method. Data were collected through observation, interviews, and documentation. The findings reveal that teachers consistently use an everyday life approach in teaching by connecting center activities to children’s real-life experiences. Teachers begin lessons with personal interactions such as greetings, asking about students’ well-being, and using concrete teaching aids aligned with the learning theme. This approach emphasizes not only learning outcomes but also enjoyable and meaningful learning processes. Teachers routinely conduct evaluations and develop new strategies to ensure the sustainability and effectiveness of the learning process. These findings reinforce the importance of consistency in using everyday approaches in early childhood education aligned with the Merdeka Curriculum philosophy.